Living on the Edge: Using and Improving Trap Crops for Flea Beetle Management in Small-Scale Cropping Systems - David George; Gordon Port; Rosemary Collier (Insects, 2019)
The use of trap crops to manage pest insects offers an attractive alternative to synthetic pesticides. Trap crops may work particularly well at smaller production scales, being highly amenable where crop diversification and reduction of synthetic inputs are prioritised over yield alone. This paper describes a series of experiments. The first was to demonstrate the potential of turnip rape (Brassica rapa L., var. Pasja) as a trap crop to arrest flea beetles (Phyllotreta spp.) to protect a main crop of cauliflower (Brassica oleracea L., var. Lateman). The subsequent experiments explored two possible approaches to improve the function of the trap crop—either by separating trap and main crop plants spatially, or by introducing companion plants of tomato (Lycopersicon esculentum Mill., cv Amateur) into the main crop. In caged field experiments, feeding damage by flea beetles to crop border plantings of turnip rape far exceeded damage to cauliflower plants placed in the same position, indicating a “trap crop effect”. Neither turnip rape plants nor cauliflower as a border significantly reduced flea beetle damage to main crop cauliflower plants, although the numbers of feeding holes in these plants were lowest where a turnip rape border was used. In similar cages, leaving gaps of 3−6 m of bare soil between turnip rape and cauliflower plants significantly reduced feeding damage to the latter, as compared to when plants were adjacent. The results of a small-scale open field trial showed that a turnip rape trap crop alone reduced flea beetle damage to cauliflower, significantly so later in the season at higher pest pressures, but that addition of tomato companion plants did not improve pest control potential.